The Evaluation of Mathematics Online Learning in Eight Grade Students of SMP Negeri 1 Sipahutar in Academic Year 2021/2022 - Tampubolon, Taruli; Sibarani, Sariayu; Sibarani, Robert (International Journal of Humanities and Education Development (IJHED), 2022)
Learning mathematics in Covid-19 (Corona Virus Disease) learning is very ineffective and cannot meet face to face directly between teachers and students, and other students Therefore, in learning during the COVID-19 pandemic, students are asked to study from home using online methods, namely through social media. This study aims to determine the ease and constraints as well as learning outcomes and the effectiveness of student learning in online learning mathematics for eight grade students of SMP Negeri 1 Sipahutar. Type of research is descriptive qualitative which takes place in SMP Negeri 1 Sipahutar. The data sources used are primary and secondary data sources. The techniques used in data collection are interview methods, observation methods, test methods, and documentation methods. The data analysis technique used is data reduction and data presentation. Based on the learning outcomes and the effectiveness of student learning seen from student learning outcomes tests showed that the percentage of classical learning completeness was 37.5%. Based on these results, mastery learning reaches the criteria of being unfavorable thus it can be concluded that online learning during the COVID-19 pandemic using the WhatsApps application in mathematics learning is not effective.